Unpacking the link between flexible work arrangements and job stress: The mediating role of Job satisfaction among highly educated employees - Gašić, Dimitrije; Berber, Nemanja; Ćurčić, Nikola; Čudanov, Mladen; Zsigmond, Tibor; Tomaš, Darko (PLOS ONE, 2025)
The main objective of this research was to investigate the mediating role of Job satisfaction in the relationship between flexible working arrangements (FWAs) and Job stress. The main research question is: what is the nature of the effect of flexible working arrangements on Job stress and Job satisfaction, the effect of Job satisfaction on Job stress and the role of Job satisfaction as mediation in the relationship between FWAs and Job stress? The methodology consists of theoretical and empirical parts. The empirical research was performed on a sample of 448 highly educated employees who operate in Serbia. Sample collection lasted from April to July 2024 via G-Forms electronic questionnaire. The proposed relationships were tested by applying PLS-SEM method via SmartPLS software. The main findings of the research are that there are positive effects of Flexible work arrangements and Job satisfaction on Job stress, and Job satisfaction has an indirect effect on the relationship between Flexible work arrangements and Job stress. The results indicated a partial mediation; a noticeable reduction of job stress was observed among employees who are sati.sfied with their jobs because of the implementation of flexible work arrangements.